High-resolution DNA methylation screening of the major histocompatibility complex in multiple sclerosis - Ma, Qin; Augusto, Danillo G.; Montero-Martin, Gonzalo; Caillier, Stacy J.; Osoegawa, Kazutoyo; Cree, Bruce A. C.; Hauser, Stephen L.; Didonna, Alessandro; Hollenbach, Jill A.; Norman, Paul J.; Fernandez-Vina, Marcelo; Oksenberg, Jorge R. (Frontiers in Neurology, 2023)
The major histocompatibility complex (MHC) region represents by far the strongest multiple sclerosis (MS) susceptibility loci. DNA methylation changes have been consistently detected at the MHC region in MS. However, understanding the full picture of epigenetic regulations of MHC in MS remains challenging, due in part to the limited coverage in the region by standard whole genome bisulfite sequencing or array-based methods. To fill this gap, we utilized a novel but validated MHC capture protocol with bisulfite sequencing and conducted a comprehensive analysis of MHC methylation landscapes in blood samples from 147 treatment naïve MS participants and 129 healthy controls. We identified 132 differentially methylated region (DMRs) within MHC regions and found they are significantly overlapped with MS risk variants.Integration of the MHC methylome to human leukocyte antigen (HLA) genetic data further indicate that the methylation changes are significantly associated with HLA genotypes. Using DNA methylation quantitative trait loci (mQTL) mapping and the causal inference test (CIT), we identified 643 cis-mQTL-DMRs paired associations including 71 DMRs possibly mediating causal relationships between 55 SNPs and MS risk.